2011
DOI: 10.1016/j.atherosclerosis.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

T cell activation predicts carotid artery stiffness among HIV-infected women

Abstract: Objectives HIV disease is associated with increased arterial stiffness, which may be related to inflammation provoked by HIV-related immune perturbation. We assessed the association of T cell markers of immune activation and immunosenescence with carotid artery stiffness among HIV-infected women. Methods Among 114 HIV-infected and 43 HIV-uninfected women, we measured CD4+ and CD8+ T cell populations expressing activation (CD38+HLA-DR+) and senescence (CD28-CD57+) markers. We then related these measures of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
91
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 30 publications
8
91
1
Order By: Relevance
“…Recent data showed that a higher frequency of activated CD8 + T cells among HIV-infected patients was associated with subclinical carotid disease. [10][11][12][13] An expansion of CD28 -CD57 + CD8 + T cells has also been described in patients with coronary artery disease compared with healthy individuals. 14,15 Finally, CD8 + T-lymphocyte depletion by anti-CD8 mAb in apoE-deficient mice fed a high-fat diet ameliorates atherosclerosis and infusion of CD8 + T lymphocytes promotes the development of vulnerable atherosclerotic plaques in lymphocyte-deficient apoE 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data showed that a higher frequency of activated CD8 + T cells among HIV-infected patients was associated with subclinical carotid disease. [10][11][12][13] An expansion of CD28 -CD57 + CD8 + T cells has also been described in patients with coronary artery disease compared with healthy individuals. 14,15 Finally, CD8 + T-lymphocyte depletion by anti-CD8 mAb in apoE-deficient mice fed a high-fat diet ameliorates atherosclerosis and infusion of CD8 + T lymphocytes promotes the development of vulnerable atherosclerotic plaques in lymphocyte-deficient apoE 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…37 A case-control study from the National Institute of Allergy and Infectious Disease cohort added weight to this finding by demonstrating no evidence for an association between T-cell activation and subsequent cardiovascular events in chronic HIV infection. 38 In contrast, Kaplan and colleagues found that markers of T-cell activation, including CD38, were associated with carotid artery stiffness 39 and increased risk of carotid plaques. 40 Our study is the first to positively correlate CD38 on CD8 T lymphocytes with a plasma marker of endothelial dysfunction, supporting the hypothesis that immune activation, and specifically T-cell activation, are central to the pathogenesis of cardiovascular disease in this population.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not observe an association between CD4 + T cell or monocyte activation with decreased brachial artery FMD, an analysis of the Women's Interagency HIV Study (WIHS) found that higher CD4 + T cell activation was associated with increased vascular stiffness, although brachial FMD was not assessed. 12,13 However, the WIHS analysis of HIV positive women included a proportion of participants either not on ART or with detectable viremia at the time of study, while all of our participants were on the same ART regimen with consistent viral suppression. 12 Activated T cells remain approximately twofold higher in ART-treated HIV-infected individuals compared to noninfected persons, 27 and it is possible that the long duration of viral suppression in our cohort (minimum of 2 years) and ART treatment (median 6.8 years in our cohort) may have engendered a T cell subset phenotype, in which CD8 + T cell activation was more representative of ongoing antigenic stimulation compared to CD4 + activation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found that increased T cell activation is associated with carotid plaque formation and intima thickness and reduced carotid distensibility in HIV-infected patients. [11][12][13][14] While the initiation of ART can improve arterial responsiveness, 15 markers of endothelial cell activation often remain persistently elevated despite the suppression of plasma viremia. 6,16,17 However, few studies have investigated how persistent innate and cellular immune activation simultaneously affect functional arterial response and endothelial activation in the context of long-term treated HIV infection.…”
mentioning
confidence: 99%